Proteomic Analysis of Effects of Spironolactone in Heart Failure With Preserved Ejection Fraction. (9th August 2022) - Javaheri, Ali; Diab, Ahmed; Zhao, Lei; Qian, Chenao; Cohen, Jordana B.; Zamani, Payman; Kumar, Anupam; Wang, Zhaoqing; Ebert, Christina; Maranville, Joseph; Kvikstad, Erika; Basso, Michael; et al.
Abstract : Background: The TOPCAT trial (Treatment of Preserved Cardiac Function Heart Failure With an Aldosterone Antagonist Trial) suggested clinical benefits of spironolactone treatment among patients with heart failure with preserved ejection fraction enrolled in the Americas. However, a comprehensive assessment of biologic pathways impacted by spironolactone therapy in heart failure with preserved ejection fraction has not been performed. Methods: We conducted aptamer-based proteomic analysis utilizing 5284 modified aptamers to 4928 unique proteins on plasma samples from TOPCAT participants from the Americas (n=164 subjects with paired samples at baseline and 1 year) to identify proteins and pathways impacted by spironolactone therapy in heart failure with preserved ejection fraction. Mean percentage change from baseline was calculated for each protein. Additionally, we conducted pathway analysis of proteins altered by spironolactone. Results: Spironolactone therapy was associated with proteome-wide significant changes in 7 proteins. Among these, CARD18 (caspase recruitment domain-containing protein 18), PKD2 (polycystin 2), and PSG2 (pregnancy-specific glycoprotein 2) were upregulated, whereas HGF (hepatic growth factor), PLTP (phospholipid transfer protein), IGF2R (insulin growth factor 2 receptor), and SWP70 (switch-associated protein 70) were downregulated. CARD18, a caspase-1 inhibitor, was the most upregulated protein by spironolactone (−0.5% with placebo versus +66.5% with spironolactone, P <0.0001). The top canonical pathways that were significantly associated with spironolactone were apelin signaling, stellate cell activation, glycoprotein 6 signaling, atherosclerosis signaling, liver X receptor activation, and farnesoid X receptor activation. Among the top pathways, collagens were a consistent theme that increased in patients receiving placebo but decreased in patients randomized to spironolactone. Conclusions: Proteomic analysis in the TOPCAT trial revealed proteins and pathways altered by spironolactone, including the caspase inhibitor CARD18 and multiple pathways that involved collagens. In addition to effects on fibrosis, our studies suggest potential antiapoptotic effects of spironolactone in heart failure with preserved ejection fraction, a hypothesis that merits further exploration.